Characterization of marine fungal communities using next generation sequencing techniques - Kristiansen, Helga Bårdsdatter (2014)
As molecular and bioinformatics techniques are used more frequently and new marine habitats are analysed, a constant increase of marine fungal diversity has been reported, suggesting that marine fungi are a diverse but somewhat ignored organism group. The overall objective of this thesis was to further increase our knowledge about fungal diversity in marine environments by (1) investigating the fungal communities in the pelagic at different depths and dates using an Illumina amplicon sequencing approach, and (2) investigating the fungal communities in sediments using a 454 shotgun metagenomic pyrosequencing dataset. From the arctic marine environment only 14.3% of the DNA amplified was of fungal origin. This demonstrated that the primer pair ITS1F-ITS2 is not fungal specific in a marine environment. In the marine sediments, fungi accounted for, on average, 13.7% of the eukaryotic reads. Yeasts dominated in the sediments samples and are probably adapted to life in anoxic marine sediments. Mortierellales (Zygomycota), which includes known marine fungi, dominated the pelagic arctic fungal communities. What may be terrestrial fungi were detected in both habitats, but it is not clear whether they were deposited and dormant in the marine environment or if they were actively growing and adapted to marine environments. The pelagic fungal communities were not structured according to location or depth, but there seemed to be a seasonal fluctuation in the pelagic communities. Lack of taxonomic coverage of fungal taxa in the reference databases proved to be one of the major obstacles in determining the fungal diversity in both studies. While my study provides insight into the fungal communities in sediments and the pelagic, it also highlights the need for improved databases and further studies with proper sampling techniques and replicates in order to determine what factors actually structures these communities and what role fungi play in the marine system.